The Influence Of Taxes Pbb-P2, Billboards, And Restaurants On Revenue Pad (Local Revenue) Mojokerto Indonesia - Saputra, Bima; Asy'ari, Muhammad Asim (CV. AFDIFAL MAJU BERKAH, 2025)
This study analyzes the effectiveness and contribution of PBB-P2 Tax, Billboard Tax, and Restaurant Tax to Local Revenue (PAD) in Mojokerto Regency for the period 2022 to 2024. Using a quantitative approach and secondary data from the Mojokerto Regency Local Government Budget Implementation Report, this study found that all three taxes consistently exceeded their annual revenue targets, thereby being classified as “highly effective.” Specifically, the PBB-P2 tax achieved an effectiveness rate of 107.45% (2022), 101.17% (2023), and 104.01% (2024), and made a significant contribution to PAD, ranging from 27.89% to 43.36% annually. Restaurant tax followed with effectiveness rates of 120.78%, 101.84%, and 112.18%, and a steadily increasing contribution from 2.74% in 2022 to 3.54% in 2024. Billboard taxes, although also highly effective at over 101% annually, contribute the least to PAD, ranging from 1.01% to 1.12%, but show a positive upward trend. These findings indicate that while all taxes are managed efficiently, their respective contributions to PAD vary, presenting an opportunity for local governments to optimize underperforming tax sectors—particularly billboard and restaurant taxes—to enhance overall PAD.